2012
DOI: 10.1016/j.psychres.2011.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia is not a stable personality trait in patients with substance use disorders

Abstract: The construct of alexithymia as a vulnerability factor for substance use disorders (SUD) is under debate, because of conflicting research results regarding alexithymia as a state or trait phenomenon. The absolute and relative stability of alexithymia were evaluated in a pre-post design as part of a randomised controlled trial, controlling for several co-variates. Assessments were done with the Toronto Alexithymia Scale (TAS-20) and the Addiction Severity Index (EuropASI) at baseline and follow-up of a 3-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 52 publications
5
41
1
3
Order By: Relevance
“…Some argue that alexithymia is better defined as a state or trait. Various findings support the view that this construct represents a stable personality trait [2, 44]. Other evidence reported that alexithymia was a state-dependent personality construct and that TAS-20 scores changed after psychotherapy [45].…”
Section: Discussionmentioning
confidence: 68%
“…Some argue that alexithymia is better defined as a state or trait. Various findings support the view that this construct represents a stable personality trait [2, 44]. Other evidence reported that alexithymia was a state-dependent personality construct and that TAS-20 scores changed after psychotherapy [45].…”
Section: Discussionmentioning
confidence: 68%
“…50 In contrast, some researchers suggest that alexithymia is a statedependent phenomenon in depressed people 51 and partly a state-dependent phenomenon in patients with substance use disorder. 52 Strong associations were also found between alexithymia and immature or maladaptive defense styles in students 53 and alcohol-dependent inpatients. 54 Students with negative emotions, such as anxiety or depression, may use the Internet to relieve these emotions externally 55,56 and may have alexithymia as a defense mechanism internally.…”
Section: Discussionmentioning
confidence: 96%
“…An alternative explanation is that alexithymic characteristics contribute to elevated psychological distress (Tolmunen et al, 2011) due to a failure to regulate distressing emotions (Berking et al, 2008). For instance, prospective studies have shown reductions in alexithymia to be largely independent of individual differences in clinical severity (de Haan, Joosten, et al, 2012;de Haan, van der Palen, Wijdeveld, Buitelaar, & De Jong, 2014;de Timary et al, 2008;Grabe et al, 2008;Luminet et al, 2001;Picardi et al, 2012). A study by Luminet et al (2001) found that following a very large reduction in clinical severity over the course of treatment, and despite a moderate reduction in alexithymia scores (mean-level), relative differences in alexithymia scores among patients remained the same (relative stability).…”
Section: Discussionmentioning
confidence: 99%